Resilience of Broken Home Children in Building Self-Efficacy among Middle School Students - Desyana, Clarisa Eka; Handayani, Arri; Lestari, Farikha Wahyu (Konseling Edukasi : Journal of Guidance and Counseling, 2023)
Resilience Of Children From Broken Homes In Building Self-Efficacy.Not all children grow up in harmonious family conditions, there are some who grow up in broken homes which will affect their resilience ability in building self-efficacy to survive in life. The fact is that not all children from broken homes are able to be resilient in building self-efficacy. The problem in this research is how resilient children from broken homes are in building self-efficacy? This research aims to determine the resilience of children from broken home family backgrounds in an effort to build self-efficacy. This type of research is qualitative phenomenological research. The research subjects were children under the age of 18 who experienced broken home conditions with a background of children from broken homes with families that were still intact but not harmonious, children from broken homes with the death of one parent, and children from broken homes with divorced parents. The results of the research showed that the three children who experienced broken home conditions had resilience in an effort to build self-efficacy. Although one of the children whose parents died had differences in the aspect of self-efficacy which was only moderate.Keywords: Resilience, Broken Home, Self Efficacy